2022
DOI: 10.1212/nxi.0000000000001161
|View full text |Cite
|
Sign up to set email alerts
|

Increased Remyelination and Proregenerative Microglia Under Siponimod Therapy in Mechanistic Models

Abstract: Background and ObjectivesSiponimod is an oral, selective sphingosine-1-phosphate receptor-1/5 modulator approved for treatment of multiple sclerosis.MethodsMouse MRI was used to investigate remyelination in the cuprizone model. We then used a conditional demyelination Xenopus laevis model to assess the dose-response of siponimod on remyelination. In experimental autoimmune encephalomyelitis–optic neuritis (EAEON) in C57Bl/6J mice, we monitored the retinal thickness and the visual acuity using optical coherence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 48 publications
1
21
0
Order By: Relevance
“…Dietrich et al. recently demonstrated that siponimod can support remyelination, presumably by modulating the polarization of microglia cells ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…Dietrich et al. recently demonstrated that siponimod can support remyelination, presumably by modulating the polarization of microglia cells ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to siponimod’s effects on the inflammatory and neurodegenerative components of MS, preclinical data also indicated that its neuroprotective mechanisms could include attenuation of axonal demyelination and promotion of axonal remyelination via oligodendrocytes [ 29 ]. Further, Jackson et al demonstrated that after insult was elicited by lysophosphotidyl choline in a rat model, fingolimod could also actively promote remyelination, suggesting a direct interaction of fingolimod with microglia, oligodendrocytes and/or astrocytes [ 30 ].…”
Section: Overview Of Available Dmtsmentioning
confidence: 99%
“…Treatment with siponimod 5 days after adoptive transfer resulted in a sparing of myelin compared with untreated controls, but with no change in oligodendrocyte numbers [ 81 ]. A study utilizing three experimental models (cuprizone and autoimmune encephalomyelitis-optic neuritis mouse models and a conditional demyelination Xenopus tadpole model) observed a protective effect of siponimod on oligodendrocytes [ 82 ]. Finally, post hoc analyses of MRI data from the phase 3 EXPAND trial also suggest that siponimod might have a beneficial effect on myelination density in patients with SPMS (see Sect.…”
Section: Preclinical Evidence For Direct Effects Of Siponimod On the Cnsmentioning
confidence: 99%
“…Basal levels of receptor gene expression are highest for S1P 1 , followed by S1P 5 , and then the other S1P receptors [ 58 ], although experimental or disease conditions can alter expression levels. Beneficial effects of siponimod in the CNS driven by shifting microglia to a regenerative state have been found [ 82 ].…”
Section: Preclinical Evidence For Direct Effects Of Siponimod On the Cnsmentioning
confidence: 99%